CONCEPTS OF PARTNERSHIP AND THREATS ON THE TERRITORY OF THE CENTRAL AND EASTERN REGION OF EUROPE - Остап’як, В. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
An attempt to consider the partnership during the "hybrid confrontation" was made. A perception of the crisis in the society as a system of global transformation, which can be described and predicted using political analysis was proposed. Political reality was considered and an attempt to consider the "local time" as an integral part of the transformation processes in the light of international relations was made. The effectiveness of the use of political partnership, as the system that is able to stabilize the flow of destructive transformations in the society was demonstrated. Transformational changed usually act as the main catalyst for the changes of the modern world. We can observe a lot of turning points in many countries, particularly in the post-Soviet space. After the collapse of the Soviet Union a sharp shift in the world politics into the era of multipolar relations took place. The breakdown of the bipolar construction of the world led to the emergence of new threats to the mankind, new challenges and new hopes for peace. Changing of foreign policy vectors implementation took place not only in the former Soviet countries, but also worldwide. Accordingly, rapid economic transformations that have been reflected by the approach to the partnership policy implementation occurred in the process of changes in the foreign and domestic policy. Changes in the economic structure of the world also led to the restructuring of social sphere in Ukraine, the Russian Federation and the EU, the US and other countries. All countries in the world faced the new threats: international terrorism, military interventions, environmental disasters, financial crises, etc. However, the biggest danger, in the author’s opinion, should be expected from the emergence of full-scale military conflicts with the use of a new type of weapons, including weapons of mass destruction. Particularly sensitive to changes in the global system are countries in transition, as well as post-Soviet countries that were the last to adapt to democratic system functioning. The way out of the crisis, including Ukraine, could be found on the terms of partnership involvement of pro-Western democracies that would stimulate the transformation processes and help to better integrate into the EU community. The Baltic countries which, using the experience of the EU, could surprisingly quickly adapt to the challenges of international relations can serve as the evidence to this. Russia has imperial ambitions, unlike the pro-Western democratic world countries. Moscow may offer its satellites only return to the command-administrative system of governance. Accordingly, this distributes Russia’s own imperial ambitions that can only exert destructive influence on political and economic spheres, both at regional and global levels. It is clear that such a partnership leads to the logical development of resistance and new systems of effective partnership aimed at anticonflict opposition to hybrid threats.